New Approach for the One-Pot Synthesis of 1,3,5-Triazine Derivatives: Application of Cu(I) Supported on a Weakly Acidic Cation-Exchanger Resin in a Comparative Study - Havránková, Eva; Csöllei, Jozef; Pazdera, Pavel (Molecules, 2019)
An efficient and simple methodology for Ullmann Cu(I)-catalyzed synthesis of di- and trisubstituted 1,3,5-triazine derivatives from dichlorotriazinyl benzenesulfonamide and corresponding nucleophiles is reported. Cations Cu(I) supported on macroporous and weakly acidic, low-cost industrial resin of polyacrylate type were used as a catalyst. The reaction times and yields were compared with traditional synthetic methods for synthesis of substituted 1,3,5-triazine derivatives via nucleophilic substitution of chlorine atoms in dichlorotriazinyl benzenesulfonamide. It was found that Ullmann-type reactions provide significantly shortened reaction times and, in some cases, also higher yields. Finally, trisubstituted s-triazine derivatives were effectively prepared via Ullmann-type reaction in a one-pot synthetic design. Six new s-triazine derivatives with potential biological activity were prepared and characterized.
Keywords: Triazines; Catalysis; katalýza; poréznost; triaziny; molekulární struktura; Copper; Porosity; Molecular Structure; měď